2020
DOI: 10.3389/fonc.2020.01584
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Microbiota in Cancerous Lung and the Contralateral Non-Cancerous Lung Within Lung Cancer Patients

Abstract: Background: The functional role of lung microbiota has attracted an accumulating attention recently, but the profile and functional role of the lung microbiota in patients with lung cancer remained largely unknown. Methods: To evaluate the association of the microbiota with lung cancer, we performed comparative analysis of the lung microbiota using 16S rRNA amplicon sequencing approach in the paired bronchoalveolar lavage fluid (BALF) samples (paired samples from cancerous lung and the contralateral non-cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 23 publications
4
12
0
Order By: Relevance
“…At the phylum level, the faecal samples of LC patients show a higher abundance in Bacteroidetes and Firmicutes compared to that of the healthy control group, similar to the study results of Yu et al 36 . but different from that of a study by Zhuo et al 37 . As we know, the Firmicutes to Bacteroidetes ratio is often used to determine health status and may indicate the bacterial population balance of the gastrointestinal tract 33 .…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…At the phylum level, the faecal samples of LC patients show a higher abundance in Bacteroidetes and Firmicutes compared to that of the healthy control group, similar to the study results of Yu et al 36 . but different from that of a study by Zhuo et al 37 . As we know, the Firmicutes to Bacteroidetes ratio is often used to determine health status and may indicate the bacterial population balance of the gastrointestinal tract 33 .…”
Section: Discussionsupporting
confidence: 70%
“…Also, an increase in gut microbiota diversity has been found in some patients with other malignant tumours, such as thyroid carcinoma, 33 gastric cancer, 34 and oesophageal cancer. 35 At the phylum level, the faecal samples of LC patients show a higher abundance in Bacteroidetes and Firmicutes compared to that of the healthy control group, similar to the study results of Yu et al 36 but different from that of a study by Zhuo et al 37 As we know, the Firmicutes to Bacteroidetes ratio is often used to determine health status and may indicate the bacterial population balance of the gastrointestinal tract. 33 Thus, we speculated that increased Firmicutes to Bacteroidetes ratio may contribute to the pathogenesis of LC.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…We did not observe a significant difference in overall microbiome composition between paired tumor and normal lung samples in our study, with composition being more similar within than between patients. Similar overall composition for paired tumor and normal lung is consistent with our previous pilot study [ 21 ] and other studies that have compared tumor and normal lung samples [ 18 , 55 , 56 , 62 65 ]. Some of these studies have observed differences in specific taxa between paired tumor and normal lung samples, including a meta-analysis of 5 studies which found decreased abundance of Actinobacteria, Corynebacterium , Lachnoanaerobaculum , and Halomonas in tumor compared to adjacent normal lung [ 66 ].…”
Section: Discussionsupporting
confidence: 91%
“…At lower taxonomic levels, we observed that species Marmoricola aurantiacus in tumor tissue was associated with worse DFS only, and an ASV from Mycobacterium vaccae in normal lung tissue was related to better survival. Mycobacterium [ 55 , 56 ] and Marmoricola [ 56 , 58 ] have been previously observed in the respiratory microbiome in other studies, but not consistently across all studies, making it unclear if these are common residents of the lung microbiome or possible contaminants. As Marmoricola was an abundant genus in our samples, its relation with worse DFS may explain the significant association of overall tumor microbiome composition with DFS in MiRKAT-S analysis.…”
Section: Discussionmentioning
confidence: 99%